EFEKTIVITAS KOOPERATIF TWO STAY-TWO STRAY TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA (FMIPA UNNES, 2012)
This research aimed to identify the effectiveness of using”two stay two stray” cooperative learning models towards students’ activities and learning achievements in classification of living things subject matter. The study was held at MTs state of Sulang, 7thgrade semester in 2011/2012.The design of research was pre-experiment with One Shoot Case Study. Samples were the class VII2, VII3 and VII4 who were collected by purposive sampling technique. The variable were ”two stay two stray” cooperative learning models, students’ activities and learning achievements in classification of living things matter. Obtained data were analyzed by descriptive quantitative methods. The results showed that the percentage of students who were active and very active in the class from all three class up to 86.67%. Completeness of students’ learning achievement was 93,33%.The conclusion from this research was that the learning of Living Things Classification using “two stay two straý” cooperative learning model was effective to improve the activity and students’ learning achievements at MTs state of Sulang. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan model pembelajaran kooperatif two stay two stray terhadap aktivitas dan hasil belajar siswa pada materi klasifikasi makhluk hidup. Penelitian dilaksanakan di kelas VII semester gasal MTs Negeri Sulang tahun ajaran 2011/2012. Rancangan penelitian ini adalah pre-experimental design dengan desain One Shoot Case Study. Sampel yang digunakan adalah kelas VII2, VII3 dan VII4 dengan teknik purposive sampling. Variabel penelitian ini adalah model pembelajaran kooperatif two stay two stray, aktivitas dan hasil belajar siswa. Hasil penelitian menunjukkan bahwa persentase siswa yang aktif dan sangat aktif secara klasikal pada ketiga kelas mencapai 86,67%. Ketuntasan hasil belajar siswa mencapai 93,33%. Data yang diperoleh dianalisis secara diskriptif kuantitatif. Kesimpulan dari penelitian ini bahwa model pembelajaran kooperatif two stay two stray efektif terhadap aktivitas dan hasil belajar siswa klasifikasi makhluk hidup di MTs Negeri Sulang.